Azərbaycan Xalq Cümhuriyyəti: “AZƏRTAC”ın yaranma zərurəti və keçdiyi yol - Ahmadov, Namiq (Muş Alparslan Üniversitesi, 2019)
The topic of this article is the hard and glorious way passed through byAzerTAc – the heritage of the Azerbaijan People’s Republic and one of the firstnews agencies in the East. The period of formation of the agency can be dividedinto 3 phases. The first phase is quite short in time. This two-month period iseven ten times smaller than the age of the Azerbaijan People’s Republiccovering the March-April of 1920. The second phase covers quite a long periodof time – the Soviet era. In fact, this period can be divided into severalphases given the turmoil in history of the Soviet state. Finally, the thirdphase covers the period when we gained our second independence. During thisperiod – in 1992, AzerTAc restored its historical name, though the first yearsof the independence were very challenging, and the agency experienced seriouseconomic difficulties due to abrupt transition to self-supporting basis. HeydarAliyev’s return to political power in Azerbaijan in 1993 marked a newdevelopment stage in AzerTAc’s activity.

Makalenin konusu Azerbaycan Halk Cumhuriyeti’nin yadigarı ve Doğu’dailk haber ajanslarından biri olan AzerTAc’ın geçtiği zor, ama şerefli yoldur.Ajansın oluşum dönemini 3 aşamaya ayırabiliriz. Birinci aşama 1920 senesininMart-Nisan aylarını kapsıyor. Milli haber ajansı ilk haberlerini bu dönemdeyayınlamaya başlamıştır. İkinci aşama zamansal açıdan uzun dönemi kapsıyor – tümSovyet Dönemi’ni. Üçüncü aşamaysa ikinci özgürlüğümüze kavuştuğumuz dönemikapsıyor. Bu dönemde – 1992 senesinde AzerTAc tarihi ismine geri dönmüştür. Amaözgürlüğün ilk yılları onun için çok zor olmuş, ajans birden bire kendibütçesinden yönetilmeye başlayınca, ciddi ekonomik sorunlar çıkmıştır. 1993senesinde Haydar Aliyev’in Azerbaycan’da siyasi hakimiyete dönüşü AzerTAc’ınfaaliyetinde yeni gelişme çağı olmuştur.
The heritage of Azerbaijan People’s Republic – AzerTAc: necessity for the establishment and the challenges it passed through
anemon
Keywords: Azerbaijan People’s Republic; AzerTAc; the Soviet-era; TASS; Information; Azerbaycan Halk Cumhuriyeti; AzerTAc; sovyet dönemi; Bilgi